Reaction Functions and the Theory of Duopoly - Friedman, J. W. (Review of Economic Studies, 1968)
Journal Article Reaction Functions and the Theory of Duopoly Get access J. W. Friedman J. W. Friedman Yale University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 3, July 1968, Pages 257–272, https://doi.org/10.2307/2296661 Published: 01 July 1968